Translation and validation study of the Polish version of the Brief Hepatitis C Knowledge Scale. - Olga Tronina; Joanna Gotlib; Piotr Małkowski; Mariusz Jaworski; Mariusz Panczyk (PLoS ONE)
Introduction Chronic hepatitis C (HCV), considered by the World Health Organization as one of the greatest epidemiological health hazards, often with asymptomatic clinical course and one which, due to scanty knowledge, remains a crucial risk factor of serious chronic HCV infection complications. The purpose of this study is to validate the psychometric properties of the Polish version of the validated Brief Hepatitis C Knowledge Scale (BHCKS_PL), developed by Balfour in 2009. Methods The study, conducted from May to July 2018, included 246 persons (68,69% females), divided into four subgroups: patients (n = 86), nursing students (n = 74), medical students (n = 28), healthcare workers (nurses and doctors; n = 58). The 19-items questionnaire contained questions designed to assess general knowledge regarding hepatitis C and the transmission risk factors. Results An evaluation by means of multiple comparisons in pairs showed that there were significant differences in the knowledge level between the group of patients and the group of nursing students (Mdn: 14.0 vs 11.0, z = 7.713, P<0.001), and between students of medicine (Mdn: 16.0 vs 11.0, z = 0.339, P<0.001) and healthcare workers (17.0 vs 11.0, z = 11.447, P<0.001). Moreover, significant differences were observed between the groups of students of nursing and medicine (Mdn: 14.0 vs 16.0, z = 3.646, P = 0.002) and healthcare workers (Mdn: 14.0 vs 17.0, z = 4.117, P<0.001). No significant differences in the knowledge level between the students of medicine and healthcare workers were observed (z = 0.377, P = 1.000). Conclusions The completed validation suggests good BHCKS_P psychometric characteristics with the internal consistency convergent and known-groups validity. The questionnaire can be used in educational practice. The obtained results of the measurement provide information about the studied person based on the total score.